Influência do uso e ocupação do solo na qualidade da água do reservatório UHE Ponte de Pedra (MT/MS) no planalto adjacente ao Pantanal - Favretto, Camila Silva (2016)
Identifying soil uses in watersheds with the presence of hydroelectric provides an amplified analysis of the factors that may influence the main watercourse. This study aimed to relate soil uses to sediment production and selection of functional phytoplankton groups for water quality of the Correntes river, which formed the reservoir of the Hydroelectric Plant Ponte de Pedra, located on the plateau adjacent to Pantanal (17o13'34.02"S, 53o40'22.12"O e 17o48'33.01"S, 55o09'04.96"O). A scientometric study was executed in SCOPUS from the conjugated terms "Water quality" "reservoirs" "functional groups"; "Water quality" "reservoirs" "bioindicator" and "Water quality" "reservoirs" soil use. The drainage network, boundary and declivity of the basin terrain, and soil uses were elaborated from LANDSAT satellite images 5, 7 and 8 using geo-processing techniques in a GIS environment. To calculation the annual sediment load (input Qst) was adopted the proposal of Carvalho et al. (2000) and Poff et al. (2010). The classification of functional groups followed Reynolds et al. (2002) reviewed by Padisák et al. (2009) and the Q calculation was proposed by Padisák et al. (2006). Using the hydro-environmental database and dominant functional groups (2005 to 2011) from eight collection points, the magnitude of the effects of the plant operation was calculated. The scientiometric survey amounted 608 publications for all three sets of words. The soil use mapping has shown historically there was a predominance of agriculture occupying up to 60% of the total area of the basin, forest class up to 31%, areas discovered up to 24%, pasture up to 11%, continental waters up to 2% and urban areas Up to 0.1%. The average annual sediment yield of the basin was 412 mg L-1, the highest value occurred in 2006 and 2011 when there was a larger area occupied by agriculture (sugarcane and soybean) and uncovered area. The basin produced on average 18,094 tons / year of liquid discharge of solids. The strong relationship (r2 = 0.96) between the inflow (68.9 to 93.9 m3 / s) and the sediment concentration demonstrate the flow determines the sediment transport and sediment production in the Correntes river. The forest classes (r = 0.98 and p = 0.002) and inland waters (r = 0.88 and p = 0.03) were correlated with the sediment loading that commit oneself to reservoir. The decrease of the forests (reduction of 20%) may have had an effect on the sediment load carried to the reservoir. The Correntes river was characterized by high luminosity, reduced concentration of nutrients, chlorophyll and phytoplankton biomass (0.41 to 1.31 mm3L-1). There were two environmental conditions: the first is in the upstream currents (COR1) and downstream of reservoir (COR 6, 7 and 8) with the occurrence of the functional groups Na, N and Y, classifying the water quality from good to excellent; The second region, the body of the reservoir was formed by the groups Na, P and MP (COR 2), next to the dam by Na and P (COR 3), followed by the groups J, Na and X1 (COR4) and by Na, P And S1 (COR5), with water quality swinging from tolerable to medium. The final analysis of the data to identify the effects of the uses and operation of the reservoir identified a decrease in turbidity, phosphorus and total sulfur of the water in relation to natural control point, so no effect was verified on the phytoplankton biomass or on the functional groups. Soil uses are influencing sediment production and water quality when it comes to phosphorus retention and sedimentation, but they were not sufficient to change the biological component since the dominant functional groups were common in the different regions analyzed in the River Currents.